Contesting Otherness: Investigating Elle Woods’ Position in Legally Blonde - Rebekah Linardi (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
The film Legally Blonde (2001), directed by Robert Luketic, follows Elle Woods, a seemingly stereotypical blonde woman who enters Harvard Law School to prove her worth. This study explores how Elle is othered and how she contests her position as the Other. Using Stuart Hall’s theory of stereotyping, particularly the concepts of otherness and contestation, this research reveals that Elle is perceived as a dumb blonde, a superficial girl, and an easy woman, which prevents her from being taken seriously in academic and professional settings. Elle challenges these social biases and the surrounding social hierarchy by using her intelligence, determination, and kindness to reverse the negative assumptions made about her. The analysis shows that otherness is not fixed and can be challenged through agency and resilience.